Peran Filsafat Ilmu dalam Pengembangan Etika Ilmiah di Masyarakat Modern - Ariqah Luthfiyah; Feri Arifin; Muzayyana Muzayyana; Ahmad Wahyudi Zein (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article discusses the role of philosophy of science in the development of scientific ethics in modern society using descriptive qualitative research methods. In the context of an increasingly complex society, the development of science and technology is often not balanced with an adequate understanding of ethics. Philosophy of science serves as a foundation for studying and reflecting on the moral values ​​that should accompany scientific progress. This study shows that philosophy of science not only provides a theoretical framework for the development of knowledge but also plays an important role in forming a critical attitude towards scientific practices that can potentially harm society. Through literature analysis, this article identifies several major contributions of philosophy of science, including reaffirming human values, developing ethical scientific policies, and promoting dialogue between science and social values. The conclusion of this study emphasizes the importance of integrating philosophy of science into scientific education and practice to create a more ethical and responsible society.